Effect of 3-subsitution of quinolinehydroxamic acids on selectivity of histone deacetylase isoforms - Samir Mehndiratta; Mei-Chuan Chen; Yuh-Hsuan Chao; Cheng-Hsin Lee; Jing-Ping Liou; Mei-Jung Lai; Hsueh-Yun Lee (Taylor & Francis Group, 2021)
A series of 3-subsituted quinolinehydroxamic acids has been synthesised and evaluated for their effect on human lung cancer cell line (A549), human colorectal cancer cell line (HCT116) and HDAC isoforms 1, 2, 6, and 8. The results indicated that substitution at C3 of quinoline is favoured for HDAC6 selectivity. Two compounds (25 and 26) were also found to be potent anti-proliferative compounds with IC50 values ranging from 1.29 to 2.13 µM against A549 and HCT116 cells. These compounds displayed remarkable selectivity for HDAC6 over other HDAC isoforms with nanomolar IC50 values. Western blot analysis revealed that compounds of this series activate apoptotic caspase pathway as indicated by cleavage of caspase 3, 8, and 9 and also increase phosphorylated H2AX thus inducing DNA double strand fragmentation in a concentration dependent manner. Flow cytometric analysis also displayed a dose dependent increase of cell population in sub G1 phase.